The Use of Sustainable Development in Urban Creative Transformations - Vignau, Mathilde (2020)
Since several decades now, creativity has been presented as a new tool for urban rehabilitation projects. Through a large number of scientific works published since the end of the 1980s, academics from all over the world pointed out the positive effects of culture and creativity on local economic development and urban attractiveness. Even if some of them have also demonstrated how limited these new tools can be by increasing gentrification, neoliberalism and socio-spatial injustices, it is quite clear now that the optimistic and enthusiastic statements coming from some scholars have undoubtedly affected urban and political decisions taken within cities worldwide. Concerning this analysis, this paper aims to present the specific case study of Toulon, a city located in the South-eastern part of France. It refers more precisely to Chalucet neighbourhood, a brand-new creative and knowledge district inaugurated in 2019, which is particularly relevant for two reasons. First, it focuses on what may be called “institutional creativity” that differs from the current idea that we often make of urban creativity through a large variety of arts, including graffiti and street art. Secondly, this specific example allows us to develop a strong connexion that exists between urban creativity and sustainability (Krueger and Buckingham, 2009, 2012). Indeed, it seems that we can sustainability consider as one of the significant factors regarding the emergence of creative cities which mainly depend on the environment and quality of life. From 2011 to 2019, the use of sustainable argument ran through the creative and knowledge district project in Toulon. For these reasons, this paper aims to present this project by underlining the links between urban creativity and sustainable development preoccupations. Moreover, it also demonstrates that the Chalucet neighbourhood in Toulon can affect local development both positively and negatively.